Faktor - Faktor yang Berhubungan dengan Tindakan Sectio Caesarea Di RS DKT: Factors Associated with Sectio Caesarea in DKT . Hospital - Sari, Ruri Maiseptya (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study is to determine the Factors who associated with Sectio caesarea in RS DKT in 2017.This study used survey analytic approach with cross sectional design. Population in this study were all labor mother in RS DKT in 2017 with the amount of 1143 people. Sampling technique used proportional random sampling, obtained sample with the amount of 296 people with sample proportion labor mother with sectio caesarea with the amount of 229 people, and labor mother pervaginam 67 people.The results of the study were: (1) from 296 mothers giving birth at DKT Hospital in 2017 there were 77.4% of women giving birth with caesarean section delivery and 22.6% of vaginal delivery mothers, 14.2% of mothers giving birth with fetal distress and 85.6% not fetal distress, 26.7% of women giving birth with DKP / CPD and 73.3% of mothers who were not DKP, 93.6% of mothers gave birth with BPJS financing and 6.4% with general financing; (2) There is a significant relationship between fetal distress and mid-category caesarean section and having a mother with a fetal distress has a risk of 1,358 times for a caesarean section compared with a mother without fetal distress; (3) There is a significant relationship between DKP / CPD with mid-caesarean section and moderate category and women with DKP / CPD have a risk of 1,447 times for caesarean section compared to mothers without PHO; (4) There is no meaningful relationship between BPJS funding and sectio caesarea.